1990
DOI: 10.1093/ajcn/51.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition supplemented with short-chain fatty acids: effect on the small-bowel mucosa in normal rats

Abstract: When enteral nutrition is excluded from animals maintained solely with total parenteral nutrition (TPN), atrophy of the intestinal mucosa is observed. Short-chain fatty acids (SCFAs) are produced in the colon by the fermentation of dietary carbohydrates and fiber polysaccharides and have been shown to stimulate mucosal-cell mitotic activity in the intestine. This study compared the effects of an intravenous and an intracecal infusion of SCFAs on the small-bowel mucosa. Rats received standard TPN, TPN with SCFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 34 publications
0
64
0
2
Order By: Relevance
“…Initial evidence for SCFAs enhancing nutritional absorption came from studies on total parenteral nutrition (TPN) for short-bowel syndrome (SBS). Supplementation of SCFAs to TPN prevented TPN associated mucosal atrophy (26) and increased the intestinal absorption of glucose (27). The underlying mechanisms include the induction of nutrient transporters such as GLUT2 in enterocytes (27,28), the induction of enterocyte proliferation and the inhibition of apoptosis (29).…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the mentioning
confidence: 99%
“…Initial evidence for SCFAs enhancing nutritional absorption came from studies on total parenteral nutrition (TPN) for short-bowel syndrome (SBS). Supplementation of SCFAs to TPN prevented TPN associated mucosal atrophy (26) and increased the intestinal absorption of glucose (27). The underlying mechanisms include the induction of nutrient transporters such as GLUT2 in enterocytes (27,28), the induction of enterocyte proliferation and the inhibition of apoptosis (29).…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the mentioning
confidence: 99%
“…SCFA are normally absorbed by the colonocyte and are either locally used as fuel for the colonic mucosal epithelial cells or enter the portal bloodstream (2,3). Production of SCFA in the bowel is important for normal intestinal biology such as water and salt absorption in the colon and energy salvation, and may also play important role in the maintenance of the intestinal barrier (4,5).…”
mentioning
confidence: 99%
“…Previous studies have also demonstrated the effect of SCFA on distal sections of the intestine (Sakata, 1987). A trophic effect in rodent small intestines was also observed with intravenous infusion of SCFA (Koruda et al, 1990). SCFA are rapidly absorbed by intestinal mucous membranes and their effects on distal sections of the alimentary tract may be explained by mediation of the autonomic nervous and cardiovascular system (Reilly et al, 1993;Frankel et al, 1994;Ichikawa et al, 2002).…”
Section: Resultsmentioning
confidence: 90%